The Effect of Organizational Culture and Perceived Organizational Support (POS) Towards Organizational Citizenship Behavior (OCB) Teacher SDK PENABUR Jakarta - Kristiani, Wahyu; Matin, Matin; Sugiarto, Sugiarto (Universitas Malikussaleh, 2019)
The purpose of this research was to study the effect of organizational culture and perceived organizational support (POS) on organizational citizenship behavior (OCB) of the SDK PENABUR Jakarta teachers. The method used in this research is a survey method, using a quantitative approach. This research was conducted on SDK PENABUR teachers, with a population of 320 people, and a sample of 178 people. Sampling uses random sampling technique. Based on the research data, it can be concluded that, first there is a positive direct effect of organizational culture on OCB. Second, there is a positive direct effect of POS on OCB. Third, there is a positive direct effect of organizational culture on POS.